Development of Mathematics Learning Devices Through Problem Based Learning Models to Improve Problem Solving Mathematics Ability Students SMP Swasta Salsa - Pratama, Reziono (Advances in Social Sciences Research Journal, 2018)
This study aims to 1) Produce products that are developing a problem-based learning tool that is valid, practical and effective in improving mathematical problem solving abilities; 2) Analyzing the improvement of students mathematical problem solving abilities in the application of problem-based learning tools. This type of research is the development using a 4-D model. The results showed that: (1) Product validity in the form of RPP, student book, LAS, and mathematical problem solving ability tests included aspects of format feasibility, language and content in a valid category; (2) Analysis of the practicality of the problem learning device developed, shows the results: a) the assessment of experts/practitioners states can be used with little revision or without revision and; b) the feasibility of learning devices in the class is included in the minimum high category and has increased by 0.16; (3) the effectiveness of the product shows: a) The completeness value of student learning outcomes increases by 10%; b) Student activity shows that all categories are at the specified ideal time tolerance interval; c) and the positive response of students is 85.7%.